Tax Avoidance in Industrial Sector Companies: What are the Influencing Factors? - Abdullah, Rahmat Rizky; Chamalinda, Khy'sh Nusri Leapatra (International Journal of Pertapsi, 2025)
This study aims to analyze and explain the effect of financial distress, capital intensity, company size, and multinationality on tax avoidance. The independent variables used in this study are financial distress, capital intensity, company size, and multinationality. The dependent variable used in this study is tax avoidance. The population in this study is all industrial sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. A purposive sampling technique was used to select the data available in this study. After the classification was carried out, 38 companies were obtained that met the sample criteria. The total sample used in this study was 190 samples. The data analysis method used is multiple linear regression. Data processing in this study was carried out using SPSS 26 software. The results of this study show that financial distress and multinationality have no effect on tax avoidance. Capital intensity and company size have an effect on tax avoidance.